Synthetic cells for phage therapy: a perspective - Kulkarni, Vishwesh; Laohakunakorn, Nadanai; Liyanagedera, Sahan B. W. (Frontiers in Cellular and Infection Microbiology, 2025)
A synthetic cell is a membrane-bound vesicle that encapsulates cell-free transcription/translation (TXTL) systems. It represents a transformative platform for advancing bacteriophage therapy. Building on experimental work that demonstrates (i) modular genome assembly, (ii) high-yield phage TXTL systems, and (iii) smart hydrogel encapsulation, we explore how synthetic cells can address major limitations in phage therapy. The promising advances include point-of-care phage manufacturing, logic-responsive antimicrobial biomaterials, and new chassis to dissect the dynamics of phage-host interactions. We also propose a roadmap for the deployment of synthetic cells as programmable and evolvable tools in the context of laboratory research and translational clinical adoption.